Malda Jelar Little Magazine-e Prokashita Chaitanya Bishayak Probondher Oitihasik Gurutto/ মালদা জেলার লিটল ম্যাগাজিনে প্রকাশিত চৈতন্য বিষয়ক প্রবন্ধের ঐতিহাসিক গুরুত্ব (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
A Little Magazine reflects the rich and diverse essence of Bengali creativity and introspection. It offers a platform for writers and poets to freely share their deepest emotions and thoughts. Though small in size, these magazines carry extensive ideas and innovative perspectives. They have played a crucial role in shaping Indian literature, particularly Bengali literature, by going beyond mainstream literary traditions. These magazines capture the essence of regional culture, customs, rituals and folklore in an organic and straightforward way. The same is true for the Little Magazines of Malda district.            Malda, located in the remote part of West Bengal, often lags in areas like education, healthcare and economy. Yet, through these Little Magazines, writers and poets strive to highlight the district's history. One significant historical focus is the arrival of Chaitanyadev in Gour. Chaitanya visited Gour on Jyeshtha Sankranti in the year 912 of the Bengali calendar, which corresponds to June 1515 in the Gregorian calendar. This event is vividly described in essays published in Malda’s Little Magazines.             While major biographies of Chaitanya, such as ‘Chaitanyabhagavat’, ‘Chaitanyacharitamrita’, and ‘Chaitanyamangal’, touch upon his visit to Gour briefly, the essayists of Malda have gone beyond these texts. They have gathered additional details and explored different perspectives on his journey. These essays also delve deeply into the socio-economic and political conditions of Gour during Chaitanya's time, the history of Ramkeli, and his association with Rup and Sanatan.              The essays in Malda's Little Magazines provide valuable insights into Chaitanyadev’s life, his impact on society, and his contributions to literature. They help readers distinguish between historical facts and legends, while also exploring instances where history and legend intertwine to form new interpretations. Since Chaitanya's visit, an annual fair has been held in Ramkeli on Jyeshtha Sankranti to honor his memory. This fair attracts visitors from across India and abroad, boosting local trade and commerce and emphasizing Chaitanya’s lasting influence. These essays have significantly enriched the study of Bengali history, especially regarding Chaitanyadev’s legacy. Their importance in understanding his life and its impact on society and culture cannot be overstated.
Keywords: Chaitanyadev; Little Magazine; Regional culture; Gour; Ramkeli; Rup-Sanatan